Paradigma Pendidikan Transformatif dalam Membangun Sekolah Dasar Berkemajuan - Muhammad Amzar; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article discusses the implementation of the transformative education paradigm in building progressive elementary schools. Elementary education plays a strategic role in shaping students’ character, critical thinking, and social awareness. However, learning practices in many schools are still teacher-centered and focused mainly on cognitive achievement. This study aims to analyze learning practices at SDN 151 Inpres Kalampa, Takalar Regency, from the perspective of transformative education. The research employed a qualitative approach using observation, interviews, and documentation techniques involving school principals, teachers, and students. The results indicate that learning practices have begun to shift toward more participatory and contextual approaches, although they are still at an early stage. Teachers have started to integrate project-based learning, environmental contexts, and character values, but challenges remain in terms of conceptual understanding, time constraints, and collaborative culture. The study concludes that transformative education has strong potential to foster progressive elementary schools through strengthening teacher capacity, contextual project-based learning, and democratic school culture.